Catalytic Hydrotreatment of Humins to Bio‐Oil in Methanol over Supported Metal Catalysts. Issue 20 (23rd October 2018) - Cheng, Ziwei; Saha, Basudeb; Vlachos, Dionisios G.
Abstract: Invited for this month's cover is the group of Dionisios G. Vlachos at the Catalysis Center for Energy Innovation (CCEI), University of Delaware. The image shows the catalytic hydrotreatment of humins byproduct derived from the aqueous processing of carbohydrates to form valuable chemicals. The Full Paper itself is available at 10.1002/cssc.201801535 . Abstract : "Humins byproduct obtained from the aqueous processing of carbohydrates can be converted to valuable chemicals…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.201801535 . View the Front Cover here: 10.1002/cssc.201802324 .